What Factors Affect the Attractiveness of Nursing Education-Nurse Teachers’ Experiences - Salminen-Tuomaala, Mari (European Journal of Applied Sciences, 2023)
Effective measures are required to mitigate the persisting nursing staff shortage. As the number of applicants for nursing education is decreasing, it is important to identify factors which can make the profession more appealing. This qualitative, observational, cross-sectional study brings in the nurse teachers’ perspective. It presents nurse teachers’ perceptions of factors that influence the attractiveness of nursing profession to potential recruits. Data was collected through online essays in May 2023 from 22 nurse teachers at a University of Applied Sciences in Finland. As in earlier studies with nurses, nurse students and nurse managers, the importance of improving the working conditions and promoting the general appreciation of nursing and nursing education was emphasized. The teachers appealed to nursing unions to speak for the importance of the profession in society rather than emphasize the poor pay and stressful working conditions.The participants also suggested improving the quality of teaching through evidence-based knowledge, individualized support, multiple modes of learning and effective teamwork between teachers. Concern was raised over the quality of the clinical training; finding clinical placements had been harder and clinical supervisors overburdened.